Nanodiscs as a new tool to examine lipid-protein interactions - Schuler, Mary A. (2013)
Nanodiscs are self-assembled discoidal fragments of lipid bilayers 8 – 16 nm in diameter, stabilized in solution by amphipathic helical scaffold protein. As stable and highly soluble membrane mimetics with controlled lipid composition and ability to add affinity tags to the scaffold protein, Nanodiscs represent an attractive model system for solubilization, isolation, purification, and biophysical and biochemical studies of membrane proteins. We overview various approaches to the structural and functional studies of different classes of integral membrane proteins such as ion channels, transporters, GPCR and other receptors, membrane enzymes, blood coagulation cascade proteins, et cetera incorporated into Nanodiscs with the special focus on the advantages provided by homogeneity, ability to control oligomerization state of the target protein and lipid composition of the bilayer. Special attention is paid to the opportunities provided by Nanodisc system for the detailed studies of the role of different lipid properties and protein – lipid interactions in the functional behavior of membrane proteins.